Working with display screen equipment - Safetycare Australia Pty. Ltd. (Australia : Safetycare Australia Pty. Ltd., 1993)
This video is an overview of issues dealing with office safety and comfort when working with display screen equipment
Accompanied by 1 trainer's manual
VCD format
Keywords: Video display terminals -- Safety regulation; Video display terminals -- Health aspects